Influence of fluid rotation on the heat transfer and pressure drop in double-pipe heat exchangers - Yildiz, C; Bicer, Y; Pehlivan, D (Elsevier Sci Ltd, 1996)
In this work the effect of propellers, which were able to rotate freely due to the force exerted by the fluid flowing through the inner pipe of the double-pipe heat exchangers, on the heat transfer and pressure was investigated expermentally. The experiments were undertaken for the Reynolds number range of 2500-15000 and for several propellers. In the system, heat-transfer rates were about 250% better than those found with the system without propellers. Thus, because of rotating the fluid, propellers and their number become influential upon heat transfer. The increase in pressure-drop changed between 500 and 1000% in comparison with that for the empty tube, depending on Reynolds number and number of propellers. (C) 1996 Elsevier Science Ltd.
Keywords: Flow